Lost in transition: the myth of Mao and the origins of COIN. (17th February 2021) - Castelli, Emanuele; Dossi, Simone; Zambernardi, Lorenzo
ABSTRACT: Mao's military teachings have greatly affected the development of modern counterinsurgency. Although the influence of Mao's doctrine on modern counterinsurgency has been examined, scholarship has failed to highlight that the reception of Mao's writings and deeds is based on a misreading of his theory and strategy. In the transition from Maoist people's war to COIN, two aspects of the former were lost. Firstly, for Mao the use of force remained the decisive instrument in war. Secondly, whereas for COIN the security of the population is a crucial goal, for Mao the population was a mere instrument that could be sacrificed if the conditions of the conflict so required.